BENTUK TARI BAKSA KEMBANG PADA ACARA PENYAMBUTAN TAMU AGUNGDI DESA PASAR LAPAN KECAMATAN AIR PUTIH KABUPATEN BATUBARA - Raja Vita Andriani S Vita Andriani (Gesture: Jurnal Seni Tari, 2013)
Baksa Kembang Dance is a dance that originated from ethnic Banjar in district especially in the village of Coal Lapan. PenelitiaAims to explain the form of dance Baksa Kembang on grand welcoming ceremony in the village Pasar Lapan Air Putih Coal County district . Based on the research that has been done , Baksa Kembang Dance is a dance that was once the Palace of the Sultan of Banjar dance . This dance is one of the ceremonial dances that used to welcome the guests who visited the palace Banjar , but this time a dance reception at the visiting dignitary in government or in the local area who visit the village Pasar Lapan . Baksa Kembang dance forms based on suitability dance with background constituent in society and form of dance based on compliance with the dance theme. Themes that are in dancing Baksa Kembang is about the joy and beauty that is transferred in the form of motion , dance clothes and property . Variety dance Baksa Kembang consists of pambukak , panghurmatan , berpandirnya , duduk basilak and gaya mat . Function dance Baksa Fireworks grand welcoming guests who expressed a sense of beauty in the form the dance moves.